The Origins of Holding-Together Federalism: Nepal, Myanmar, and Sri Lanka - Breen, Michael G. (2017)
Theories on the origin of federalism generally only apply to coming-together federalism. In Asia, some states introduced federalism following decolonization to hold together multiethnic communities, but others centralized and pursued a nation-building agenda. Federalism was not established in Asia again until Nepal’s new constitution of 2015. Why has federalism been resisted and what causes its institutionalization? Using the cases of Nepal, Myanmar, and Sri Lanka, I show that a moderate secession risk, together with a substantive peripheral infrastructural capacity, are necessary conditions for the establishment of holding-together federalism. A high secession risk prevents the formation of an alliance between minority ethnic groups and regime change agents from the dominant ethnic group, which I argue is the key mechanism for federalization in these contexts. A bargain with the core results in quasi-federalism for regime maintenance. Conversely, demands for federalism are too easily repressed when secession risk is low.